Frequency and Severity of Head Injury Among Motorcycle Riders With and Without Helmet Use - Siddiqui, Mubashara Waheed; Gaziani, Mehak Hafiz; Ahmed, Zohaib (Biological and Clinical Sciences Research Journal, 2025)
Related injuries are a growing public health concern worldwide, particularly head injuries, which are a leading cause of death and long-term disability among riders. Despite strong evidence supporting the protective benefits of helmets, helmet usage remains inconsistent, especially in low- and middle-income countries. Understanding the frequency and severity of head injuries in riders with and without helmets is essential for guiding safety regulations, promoting helmet use, and reducing the burden of traumatic brain injuries due to motorcycle accidents. Objective: The main objective of the current study was to determine the frequency and severity of head injury among motorcycle riders with and without helmet use presenting at the emergency ward of a tertiary care hospital. Methods: This cross-sectional study was conducted from November 15, 2024, to February 28, 2025, in the Department of Neurosurgery, Liaquat National Hospital & Medical College, Karachi. Participants of both genders, aged between 18-60 years, who were motorcycle riders or pillion riders presenting at the emergency ward with road accidents were included in this study. Mentally disabled patients and cases in which obtaining consent was not possible because unconsciousness of patients and the absence of their attendants were excluded from the current research study; the data were analyzed by using SPSS version 27. Results: A total of 195 motorcycle drivers injured in road accidents were included in the study; the mean age (years) of all patients was 33.24±15.73, and 80.5% (n=157) were male. Motorcycle male drivers with and without helmets presented as 88(89.8%) & 69(71.1%) compared with the female drivers as 10(10.2%) and 28(28.9%), p-value of 0.001. Glasgow Coma Scale (GCS) scores showed that motorcycle drivers with and without helmets were more often in mild (GCS-15) as 66 (67.3%) versus 27 (27.8%), p-value < 0.000. The moderate (GCS Score 9-12) severity of head injury was 4 (4.1%) versus 12(12.4%), respectively. Severe (GCS Scores 3-8) were observed as 8 (8.2%) compared to 24 (24.7%) with a statistically significant p-value < 0.005. Conclusion: The study shows that helmet use among motorcycle drivers significantly reduces the severity of head injuries. Riders who used helmets had a higher rate of mild Glasgow Coma Scale (GCS) scores and a lower number of severe injuries compared to those without helmets.